Green Synthesis of Nickel Nanoparticles and their Application of Removal of Aliphatic Hydrocarbons from Crude Oil - Sadaa, Ahmed Makki; Al Abdullah, Zainab Taha (Iraqi Journal of Science, 2021)
Nickel nanoparticles (Ni-nanoparticles) were incorporated as an antecedent utilizing nickel acetate and as a reducing agent, extraction plantApiumgraveolens. The reason fo choosing this plant over many other is because it is easily accessible, carries many antioxidants, non-toxic, and there are no dangerous residues and stabilizing agent at 60℃ under stirrer. The progress of the reaction was monitored by observing a change in color of the obtained solution. The UV–Vis utilized to screen the development of Ni-nanoparticles inside a surface plasmon band (SPB) at 275 nm gives a phantom mark appropriate to the arrangement of nanoparticles. Examining the electron microscope (SEM) photos showed the Ni-nanoparticles to be of cubic shape with sizes in te range of (6-45 nm). GC-MS s spectra were utilized to show the debasement when the expansion of nickel nanoparticles. The most noteworthy accessibility of aliphatic mixes at the hour of (1.3, 1.46, 1.62, 12.04) min. In the interim after the expansion of nanoparticle, the outcomes show a high bounty at (1.29, 2.1) min. The importance of this research lies in the possibility of breaking large organic compounds into simpler compounds, as the presence of large organic compounds with high molecular weights leads to pollution of sea and ocean waters when poured into it as a result of sea transport.